Loss Estimation of Protected Forest Damage and Its Impact on Fishery Sector in Goa Cina Beach, South Area of Malang Regency - Harsuko Riniwati; Nuddin Harahab; Zainal Abidin (Sekolah Pascasarjana Universitas Brawijaya, 2016)
Goa Cina is one ofÂ magnificent beach destinations in the South Area of Malang Regency which attracts local and foreign tourists. Generally, there are two kinds of tourism management namely ecoturism based and masstourism based. However, Goa Cina implements masstourism based management. Thus it needs an area to build tourism facilities and infrastructures. The ideal functions ofÂ protected forest had conversed into buildings such as parking lots, stalls, religious buildings, restrooms, etc. The damage of protected forest caused by its missing functions contributes to some losses. The aims of this research were to: 1) count the loss as the impact of protected forest conversion in Goa Cina which turned into tourism facilities and infrastructures; 2) analyze its impact on fishery production. The data were collected by conducting in-depth interview with the key informant and finding secondary data. The resultÂ indicated that the conversion of protected forest into tourism facilities and infrastructures caused ecological and economic loss and it needed massive ecological recovery. The fishery production also decreased due to sedimentation of saltwater. It is suggested that ecotourism should be considered for tourism development instead of masstourisnm.